IMPACT OF PERIODONTAL HEALTH STATUS ON THE ORAL HEALTH RELATED QUALITY OF LIFE IN SULAIMANI CITY BY USING ORAL HEALTH IMPACT PROFILE (Mustansiria Dental Journal, 2024)
Aim:The objective of this study is to create a valid and reliable Kurdish version of Oral Health Impact Profile-14 (OHIP-14) and to find the impact of periodontal health status on oral health related to quality of life (OHRQoL).Method: OHIP-14 was translated and checked for validity and reliability during the pilot study which involved 39 participants. After validation of the newly created Kurdish version of OHIP-14, 323 individuals participated in this questionnaire-based cross-sectional study which involved documentation of their demographics and periodontal clinical parameters for all participants by the researcher using William’s periodontal probe. The newly fabricated Kurdish version of OHIP-14 was filled by the participants themselves.Results: Among participants, the total mean of OHIP-14 and the mean values of all subscale scores significantly increase with increasing the severity of periodontal diseases (P≤ 0.05) except for psychological discomfort, and physical disability.  It was found that there was a statistically significant strong positive correlation between periodontal parameters (PI, BI, PPD, and CAL) and quality of life (p